2007
DOI: 10.1093/pcp/pcm090
|View full text |Cite
|
Sign up to set email alerts
|

The Jasmonate-Induced Expression of the Nicotiana tabacum Leaf Lectin

Abstract: Previous experiments with tobacco (Nicotiana tabacum L. cv Samsun NN) plants revealed that jasmonic acid methyl ester (JAME) induces the expression of a cytoplasmic/nuclear lectin in leaf cells and provided the first evidence that jasmonates affect the expression of carbohydrate-binding proteins in plant cells. To corroborate the induced accumulation of relatively large amounts of a cytoplasmic/nuclear lectin, a detailed study was performed on the induction of the lectin in both intact tobacco plants and excis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 51 publications
0
46
0
2
Order By: Relevance
“…62 Plant lectins are induced by elicitors as an induced response to various stresses. 68 JA induced the expression of NICTABA lectin in tobacco leaves. 68,69 Induction of NICTABA by herbivores infestation including S. littoralis, Manduca sexta L. and Tetranychus urticae Koch has been reported in tobacco plants.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…62 Plant lectins are induced by elicitors as an induced response to various stresses. 68 JA induced the expression of NICTABA lectin in tobacco leaves. 68,69 Induction of NICTABA by herbivores infestation including S. littoralis, Manduca sexta L. and Tetranychus urticae Koch has been reported in tobacco plants.…”
mentioning
confidence: 95%
“…68 JA induced the expression of NICTABA lectin in tobacco leaves. 68,69 Induction of NICTABA by herbivores infestation including S. littoralis, Manduca sexta L. and Tetranychus urticae Koch has been reported in tobacco plants. 69 Expression of a mannose-binding jacalin-like lectin called Hessian fly, Mayetiola destructor (Say) responsive protein 1 (HFR1), and two chimerolectin-like proteins called HFR2 and HFR3 have been reported to be induced by the larvae of Hessian fly, M. destructor in wheat.…”
mentioning
confidence: 95%
“…All these lectins are classified into twelve lectin families . Conditions that can induce lectin expression include salt stress (Zhang et al, 2000), pathogen infection (Qin et al, 2003), jasmonic acid treatment (Lannoo et al, 2007) and insect herbivory (Subramanyam et al, 2008;Vandenborre et al, 2009a, b). In contrast to the classical lectins that are usually stored in vacuoles, the inducible lectins often locate to the nucleus and the cytoplasm of the plant cell.…”
Section: What Are Lectins?mentioning
confidence: 99%
“…These effects may also be due to secondary effects (like gene expression or the activation/inactivation of certain enzymes) of the lectins in planta. Lannoo et al (2007) have shown that the expression the tobacco lectin called Nictaba was induced upon jasmonate treatment. More recently, Vandenborre et al (2009a, b) showed that Nictaba-expression was also induced by feeding of S. littoralis, which in turn results in elevated jasmonate levels in the leaf tissue.…”
Section: Lectins With Inducible Expressionmentioning
confidence: 99%
“…The expression of lectins/hemagglutinins 14 and protease inhibitors 11 in plants is sensitive to stress factors and environmental variations, therefore they can be regulated and induced in response to attack from insects and other pathogens. For example, tobacco leaves normally express very low levels of lectin, however, when treated with jasmonates or insect herbivory, expression of the lectin is up-regulated 15,16 . The content of lectins/hemagglutinins and protease inhibitors is more abundant in legumes compared with other plants.…”
Section: Introductionmentioning
confidence: 99%